A short tale about a long dog - Winkler, Henry, 1945-; Oliver, Lin (Winkler, Henry, 1945- Here's Hank, 2014)
Rescuing a Dachshund from an animal shelter after convincing his skeptical father to get the family a dog, Hank struggles to prove his trustworthiness after his new canine friend gets loose at the park.